2007
DOI: 10.1007/s00436-007-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

First occurrence of Culicoides obsoletus-transmitted Bluetongue virus epidemic in Central Europe

Abstract: In August 2006, Bluetongue virus disease (BTD) was detected for the first time in the Netherlands, Belgium, Germany and Northern France. Serological tests as well as reverse transcriptase polymerase chain reaction (RT-PCR) proved the occurrence of Bluetongue virus (BTV) in diseased sheep and cattle, and the virus was identified as serotype 8. Therefore, the search for possible vectors was immediately initiated in the outbreak region in Germany. Traps with automatically regulated ultraviolet light lamps were pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
135
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(140 citation statements)
references
References 14 publications
3
135
0
2
Order By: Relevance
“…are vectors of BTV (Reoviridae: Orbivirus), a virus that can replicate in any ruminant, first detected in Central Europe in 2006 (Mehlhorn et al 2008). C. obsoletus, C. pulicaris and C. scoticus are considered the main vectors of BTV in Europe and their bloodmeals derived only from livestock (Mehlhorn et al 2007, Bartsch et al 2009). Santiago-Alarcon et al (2012) found C. obsoletus, which has previously been found in Germany, and together with C. scoticus and C. pulicaris, has been feeding mainly on humans.…”
Section: Discussionmentioning
confidence: 99%
“…are vectors of BTV (Reoviridae: Orbivirus), a virus that can replicate in any ruminant, first detected in Central Europe in 2006 (Mehlhorn et al 2008). C. obsoletus, C. pulicaris and C. scoticus are considered the main vectors of BTV in Europe and their bloodmeals derived only from livestock (Mehlhorn et al 2007, Bartsch et al 2009). Santiago-Alarcon et al (2012) found C. obsoletus, which has previously been found in Germany, and together with C. scoticus and C. pulicaris, has been feeding mainly on humans.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural studies using olfactometers or wind or flight tunnels in which a specific number of biting insects are released are very rare (Bhasin et al, 2000b) due to the difficulty of obtaining a sufficient number of insects, given the complexity of maintaining many Culicoides species of interest under controlled conditions. Only a few speciesof limited interest in northern Europe -are commonly bred (Jones, 1964;Fahrner and Barthelmess, 1988;Kremer and Lienhart, 1998), and these do not include species of the subgenus Avaritia (particularly Culicoides obsoletus Meigen 1818), considered to be vectors of BTV and SBV (Mehlhorn et al, 2007;Carpenter et al, 2008;Hoffmann et al, 2009;De Regge et al, 2012;Elbers et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From 1998 through 2006, a total of 5 serotypes (1, 2, 4, 9, and 16) became established in southern Europe (5), but they were kept confi ned to this area, most likely because their main insect vector, C. imicola, has never been detected north of the Alps in Europe (6). A BTV-monitoring program in cattle herds has been in effect in Switzerland since 2003 in Ticino Canton, south of the Alps (7)(8)(9). However, no BTV has been detected until now in this region of the country.…”
mentioning
confidence: 99%
“…In 2006, BTV serotype 8 (BTV-8) of likely African origin was introduced into Belgium by an as yet unknown mechanism (8). This virus spread throughout many northern European countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation